Sunnah Schools in Jakarta Greater Area: Dakwah, Education, and the Changing Face of Urban Muslim Communities in Indonesia - Atik Yuliyani; Dadi Darmadi; sadawi sadawi; M. Hafid; Asmui Asmui (TARBIYA: Journal of Education in Muslim Society, 2022)
AbstractThis qualitative study examines the emergence of sunnah schools and their influence on the development of educational institutions among urban Muslim communities in Indonesia. Three key aspects were explored: (1) the important figures and main actors in establishing sunnah schools, (2) the content and materials used and developed in these schools, and (3) the local community response to their establishment. The study was conducted in the Jakarta Greater Area (Jabodetabek) area, encompassing South Tangerang, Depok, and Bogor Regency. The findings reveal that while sunnah schools have similarities with public schools in general education, there are significant differences in religious education, particularly in the areas of tauhid, fiqh, and other religious sciences according to the Salafi manhaj. In addition to adopting the curriculum of the Indonesian Ministry of Education and Culture, sunnah schools also use some special materials, including extracurricular activities such as horse riding and archery, which are considered part of the sunnah of the Prophet. The study concludes that the growth of sunnah schools is closely linked to the dynamics of educational institutions, changes in lifestyle trends, and the development of identity politics in urban Muslim communities in Indonesia.AbstrakPenelitian kualitatif ini mengkaji kemunculan sekolah sunnah dan pengaruhnya terhadap perkembangan lembaga pendidikan di kalangan masyarakat muslim perkotaan di Indonesia. Tiga aspek kunci yang diteliti: (1) tokoh penting dan aktor utama dalam pendirian sekolah sunnah, (2) konten dan materi yang digunakan dan dikembangkan di sekolah sunnah tersebut, dan (3) tanggapan masyarakat setempat terhadap pendiriannya. Kajian lapangan dilakukan di wilayah Jabodetabek, meliputi Kota Tangerang Selatan, Depok, dan Bogor. Temuan penelitian menunjukkan bahwa sementara sekolah sunnah memiliki kesamaan dengan sekolah umum dalam pendidikan umum, ada perbedaan yang signifikan dalam pendidikan agama, khususnya di bidang tauhid, fikih, dan ilmu agama lainnya menurut manhaj Salafi. Selain mengadopsi kurikulum Kementerian Pendidikan dan Kebudayaan RI, sekolah sunnah juga menggunakan beberapa materi khusus, antara lain kegiatan ekstrakurikuler seperti berkuda dan memanah yang dianggap sebagai bagian dari sunnah Nabi. Kajian ini menyimpulkan bahwa pertumbuhan sekolah sunnah sangat erat kaitannya dengan dinamika lembaga pendidikan, perubahan tren gaya hidup, dan perkembangan politik identitas masyarakat muslim perkotaan di Indonesia.